2012
DOI: 10.1111/j.1467-8535.2012.01319.x
|View full text |Cite
|
Sign up to set email alerts
|

A group decision approach to developing concept–effect models for diagnosing student learning problems in mathematics

Abstract: Diagnosing student learning barriers has been recognized as the most fundamental and important issue for improving the learning achievements of students. In the past decade, several learning diagnosis approaches have been proposed based on the concept–effect relationship (CER) model. However, past studies have shown that the effectiveness of this model heavily depends on the concept relationship knowledge provided by the domain experts (eg, experienced teachers or educators for a specified subject); ie, the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…The second part F 2 contained three concepts and six questions. The third part F 3 [6,6,8,10], the crisp output value for learning achievement was 10.33. Table 3 shows the respective ranges of crisp output values for evaluating learning achievement.…”
Section: Building a Range Of Crisp Output Values For Evaluating Learning Achievementmentioning
confidence: 99%
See 1 more Smart Citation
“…The second part F 2 contained three concepts and six questions. The third part F 3 [6,6,8,10], the crisp output value for learning achievement was 10.33. Table 3 shows the respective ranges of crisp output values for evaluating learning achievement.…”
Section: Building a Range Of Crisp Output Values For Evaluating Learning Achievementmentioning
confidence: 99%
“…The traditional interpretation would be that the student understood 87% of the tested concepts. Figure 8 shows that, according to the learning achievement analysis by FL-GLH [F 1 , F 2 , F 3 , F 4 ] was equal to [5,5,8,8], and the crisp output value for learning achievement was 9.58. Based on the range of crisp output values in Table 3, student 4 understood the concepts up to interval F 4 (concepts C 10 -C 11 ).…”
Section: Practical Applications Of the Fl-glh In Finding Student Learning Barrier Pointsmentioning
confidence: 99%
“…Concept maps are usually used in educational settings in three ways: (1) Instructional guidance: the concept maps generated by educational experts or instructors are used as a knowledge map for guiding students to learn (Charsky & Ressler, 2011;; (2) Assessment tool: the concepts developed by students are assessed and scored to find their misconceptions or evaluate their knowledge structure (Hwang, Panjaburee, Triampo, & Shih, 2013;Panjaburee, Triampo, Hwang, Chuedoung, & Triampo, 2013); (3) Knowledge organizing tools: concept maps are used as a tool for helping students organize what they have learned. Teachers can either ask students to complete a partially-developed concept map Lin, 2012; or develop a new concept map from the beginning (Charsky & Ressler, 2011;Hamza & Wickman, 2013;Novak, 2010).…”
Section: Concept Mapsmentioning
confidence: 99%
“…Panjaburees, Triampo, Hwang, Chuedoung and Triampo (2013) used a novel technique to present concept weights for each test item and a learning-preference style for each learner. In addition, previous studies have been conducted that integrate the opinions of multiple experts on learning-diagnosis enhancement (Hwang, Panjaburee, Triampo & Shih, 2013a;Panjaburee, Hwang, Triampo & Shih, 2010;Wanichsan, Panjaburee, Laosinchai, Triampo & Chookaew, 2012). These studies have revealed the importance of providing diagnostic information to individual students based on their learning status.…”
Section: Practitioner Notesmentioning
confidence: 99%